Predictors of breastfeeding self-efficacy among postpartum women in RSUD IA Moeis Samarinda - Nur Hastuti Fitria; Wirapuspita Wisnuwardani Ratih; Kamaruddin Iriyani (BIO Web of Conferences)
Background: WHO recommends the practice of early initiation and exclusive breastfeeding for the first 6 months of life followed by breastfeeding with complementary foods up to 2 years of age. However, currently, the global prevalence of breastfeeding in infants less than 6 months of age is under 50%. Objective: This study aims to predict the factors associated with breastfeeding self-efficacy in RSUD IA Moeis. Methods: A cross-sectional study with multiple logistic regression tests were used to analyze 56 postpartum women. Key variables analyzed included breastfeeding experience and observation of others, adjusted for occupation, education, verbal persuasion, and physical-emotional conditions. Result: Variables associated with Breastfeeding Self Efficacy (BSE) were breastfeeding experience (p-value 0.023) and observation of others (p-value 0.002) adjusted by occupation, latest education, verbal persuasion, and physical emotional conditions. The most dominant variable is the observation of others with Odds Ratio = 61.107 (95% CI OR = 5.478- 711.504). Conclusion: Observation of others is the strongest predictor of breastfeeding self-efficacy among postpartum mothers at RSUD IA Moeis. Mothers who observed others successfully breastfeeding were 61 times more likely to have high BSE than those who did not. Keyword: Breastfeeding self-efficacy, breastfeeding experience, postpartum, sociodemographic.